Care and Migration: International Conference, Goethe University and Cornelia Goethe Centrum in Frankfurt. 23rd–24th April 2009, Frankfurt, Germany. - Ezzeddine Lukšíková, Petra (Lidé města, 2009)
Working woman are traveling the globeas never before. Each year millions leave their homes and their families in Third World countries for jobs in homes and nurseries and as babysitters of the First World.